Auditory perceptual processing during musical imagery: An event-related potential study. (25th September 2021) - Teshima, Konomi; Ishida, Kai; Nittono, Hiroshi
Highlights: Auditory evoked potentials were recorded while participants watched silent music videos. Participants were asked to form auditory imagery of the song based on the video. Musical excerpts from the on-screen video elicited a smaller N1 than those from a different video. In contrast, later processing was enhanced for imagery-matched musical excerpts. Abstract: The perceptual processing of a sound is facilitated when the sound matches auditory imagery. Previous studies have shown that auditory imagery and actual sound activate the auditory cortex in a similar fashion. To investigate whether auditory imagery is a modality-specific representation or an amodal representation, the current study examined how watching silent music videos affected the auditory processing of sound excerpts. Twenty university students were asked to form musical imagery of Japanese popular songs while watching the official music videos. Event-related brain potentials were recorded in response to short sound excerpts from the on-screen video or from a different video. The results showed that the amplitude of the exogenous N1 component (90–110 ms) was smaller for imagery-matched than for unmatched sound excerpts. The electrical source of the difference was estimated in the auditory cortex. After the N1, the matched excerpts elicited a larger late positive potential (400–800 ms) than the unmatched excerpts. These findings suggest that auditory imagery involves modality-specific neural processing and that imagery-matched sounds are processed efficiently at an early stage, inducing additional cognitive processing at a later stage.